PENGARUH PERTUMBUHAN PENJUALAN, EARNING PER SHARE, DAN KEBIJAKAN DIVIDEN TERHADAP HARGA SAHAM - Sari, Oktavia Kartika; Sapari, Sapari (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis study is aimed to test whether the sales growth, earnings per share, and dividend policy influence the stock prices of the property and real estate companies which are listed in Indonesia Stock Exchange. This research uses secondary data in the annual report of property and real estate companies which are listed in Indonesia Stock Exchange in 2011-2015 periods. The data analysis technique has beenn done by using multiple linear regressions analysis and the data examination is normality test and classic assumption test which consists of heteroscedasticity test, multicollinearity test, and autocorrelation test. The result of the research shows that sales growth has no significant influence to the stock prices. Earnings Per Share and dividend policies have significant influence to the stock prices which means that the size of the profits which has been generated by the company give influence to the stock prices. When corporate profits is high, the stock price increases. Dividend policy in this case concern about the attitude of the company regarding the use of profits are the rights of the investors. If the dividend increases, the stock prices also increases.Keywords: sales growth, earnings per share, dividend policy, stock prices